2016
DOI: 10.1016/j.pbb.2016.11.003
|View full text |Cite
|
Sign up to set email alerts
|

N -phenylpropyl- N ′-substituted piperazines occupy sigma receptors and alter methamphetamine-induced hyperactivity in mice

Abstract: This study examined the effect of the N-phenylpropyl-N´-substituted piperazine ligands SA4503 (3,4-dimethoxyphenethyl), YZ-067 (4-methoxyphenethyl), YZ-185 (3-methoxyphenethyl) and Nahas-3h (4-methoxybenzyl) on methamphetamine-induced hyperactivity in mice. In a previous study in rats, SA4503 increased methamphetamine-induced hyperactivity at a lower ligand dose and enhanced it at a higher dose. The other ligands have not been investigated in this assay. Presently, mice were administered sigma ligands, and spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Hence, opipramol, in the long term, behaves as a partial agonist and protects from a relapse. Moreover, Miller et al showed that σ‐1R ligands might act as agonists or antagonists depending on their dose 37 . Furthermore, σ‐1R can be expressed as either a monomer or an oligomer, each of which determines it being an antagonist or agonist by the substances bound to it 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Hence, opipramol, in the long term, behaves as a partial agonist and protects from a relapse. Moreover, Miller et al showed that σ‐1R ligands might act as agonists or antagonists depending on their dose 37 . Furthermore, σ‐1R can be expressed as either a monomer or an oligomer, each of which determines it being an antagonist or agonist by the substances bound to it 38 .…”
Section: Discussionmentioning
confidence: 99%
“…All ligands tested had high affinity for the σ 1 R and no appreciable affinity for DAT. They found that higher doses of the compounds attenuated METH-induced (0.5 mg/kg) locomotor activity, whereas lower doses potentiated it (Miller et al, 2016). Utilizing a different selective σ 1 R agonist, our laboratory recently revealed that 8 mg/kg PRE-084 attenuates acute METH-stimulated (2 mg/kg) locomotor activity.…”
Section: Sigma-1 Receptor and Methamphetaminementioning
confidence: 99%
“…Administration of the selective σ 1 R agonist SA4503 dose dependently affected METH-induced (0.5 mg/kg) locomotor activity with lower doses enhancing hyperactivity and higher doses inhibiting it (Rodvelt et al, 2011b). More recently, Miller et al, 2016 investigated the effect of different N-phenylpropyl-N′-substituted piperazine ligands, including SA4503, on METH-induced hyperactivity (Miller et al, 2016). All ligands tested had high affinity for the σ 1 R and no appreciable affinity for DAT.…”
Section: Sigma-1 Receptor and Methamphetaminementioning
confidence: 99%